KEANEKARAGAMAN ARTHROPODA TANAH DI HUTAN PENDIDIKAN GUNUNG WALAT (Diversity of Soil Arthropods in Gunung Walat Education Forest) - Lailan Syaufina; Noor Farikhah Haneda; Asri Buliyansih (Department of Forest Resources Conservation and Ecotourism - IPB University, 2007)
Astudy was conducted to investigate the difference in abundance, richness, diversity and evenness of soil arthropods in Gunung Walat Education Forest, Sukabumi, West Java. Sampling was done in two difference habitats, e.g. burn and unburn habitat. A total of 1280 individuals from 40 families and 16 orders were collected by soil and litter extracting (Berlesse funnel). The biodiversity indices indicated that unburn habitat had a higher indices than that of burn habitat.Keywords: Diversity, Berlesse funnel, Forest Health Monitoring, unburn, soil arthropods